VO#045 Quotation for special-shaped planter bench rev.02 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmitted quotation for the special-shaped planter bench work of BRACU new campus project.